Coexistence of copper and fiber unbundling: Access charges and investment incentives - Markos Tselekounis; Georgia Orfanou; Dimitris Varoutas (International Telecommunications Society (ITS), 2014)
We study the impact of the access charges of copper and fiber unbundling on an incumbent's incentives to invest in fiber access networks. Once the fiber deployment is in place, the incumbent and the entrant compete for consumers in both copper and fiber markets. We show that when the regulator can freely set either the copper or the fiber access charge, there is a positive correlation between the fixed fiber (respectively, copper) access charge and the copper (respectively, fiber) access charge that maximizes the incumbent's profit after the investment. On the contrary, when the regulator is free to set both access charges, the incumbent's profit is an increasing function of both access charges. However, the decision of the incumbent to undertake the investment in fiber deployment is not only affected by its profit after the investment, but also by the opportunity cost of the investment. This cost is reflected by the profits that the incumbent earns when it does not invest in fiber access networks, and hence, the two firms compete for the provision of only copper-based services. We find that the optimal regulatory policy in terms of investment incentives is to set the copper access charge at the cost of providing the access to the copper access network and the fiber access charge at the level that maximizes the incumbent's profit after the investment. It should be noted that the proposed regulatory policy confirms the methodology of the EC Recommendation (2013/466/EU) for setting the copper and fiber access charges in order to promote competition and enhance the broadband investment environment.
Keywords: L51; L96; 330; Access regulation; Copper unbundling; Fiber unbundling; Investment incentives; Telecommunications